The role of dual antiplatelets in geographic atrophy secondary to non-neovascular aged-related macular degeneration - Chantarasorn, Yodpong; Smitthimathin, Warin; Vorasayan, Pongpat (Frontiers in Ophthalmology, 2022)
Background: To evaluate the effects of dual antiplatelets on progression of geographic atrophy (GA) secondary to age-related macular degeneration (AMD), and to determine additional factors predicting rapid GA growth. Material and Methods: In this retrospective cohort study, patients with unifocal GA were consecutively enrolled (one eye per patient) from 2018 to 2021. The patients were categorized as 1. those receiving dual antiplatelet therapy containing a daily dose of 75 mg clopidogrel plus 81 mg aspirin (DAPT group), and 2. those not receiving DAPT (control group). Areas of GA, based on red-filtered fundus autofluorescence, were measured at baseline, and at 3, 6, and 12 months. The primary outcome was absolute 12-month changes in the square root (SQRT) area. Results: One eye in each group developed neovascular AMD and was excluded from the analysis. The DAPT (24 eyes) and control (22 eyes) groups had comparable age and baseline SQRT area (1.2 ± 0.27 and 1.8 ± 0.41 mm, respectively; p adjusted for age = 0.23). At 12 months, after controlling for age and the presence of soft drusen or reticular pseudodrusen, patients receiving DAPT had fewer changes in the SQRT area than that of the control group (0.097 vs. 0.17 mm; p = 0.02). The presence of drusen significantly predicted increased GA growth and choroidal thickness reduction. Conclusions: Routine uses of dual antiplatelets were associated with decelerating GA growth. Drusen-associated GA may represent a generalized form of choroidal vascular alterations.